BARIUM CYCLING IN SHALLOW SEDIMENT ABOVE ACTIVE MUD VOLCANOES IN THE GULF OF MEXICO - Castellini D.G.; Dickens G.R.; Snyder G.T.; Ruppel C.D. (My University, 2006)
Methane and other hydrocarbons fluxing upward through deep-marine sediment may strongly impact the cycling of Ba near the seafloor. Piston cores across two mud volcanoes in the northern Gulf of Mexico (GOM) were therefore examined to understand Ba cycling at regions of intense hydrocarbon gas expulsion. Pore waters were analyzed for dissolved Cl-, SO42- and Ba2+, and sediment samples were analyzed for their extractable Ba contents. These data clearly show that saline fluids charged with hydrocarbons and dissolved Ba2+ (but lacking SO42-) advect from depth and profoundly influence the Ba cycle in shallow sediment. Close to the seafloor, several processes occur over time. Usually, anaerobic oxidation of methane (AOM) and other hydrocarbons in the sediment consumes dissolved SO42- diffusing from bottom water. As a consequence, focused CH4 fluxing produces a sulfate-hydrocarbon transition (SHT) that shoals across the mud volcanoes. Dissolved Ba2+ crossing this horizon reacts with SO42-, precipitating Ba fronts composed of barite immediately above the SHT. Smooth barite-rich carbonate nodules might form when this process remains at the same sediment horizon from extended time. Sometimes, however, venting releases dissolved Ba2+ into the water column, which induces barite precipitation onto the seafloor around the mud volcanoes. Episodic venting may also form and break carbonate crusts on the seafloor, producing rocky carbonate nodules cemented with barite. For both fronts and nodules, burial past the SHT leads to barite dissolution, release of dissolved Ba2+, and amplification of the shallow Ba cycle. © 2005 Elsevier B.V. All rights reserved.
Keywords: ANAEROBIC OXIDATION OF METHANE; BARITE; CARBONATE NODULE; GULF OF MEXICO; HYDROCARBONS; MARINE BARIUM CYCLE; METHANE; MUD VOLCANO; SULFATE